Association of Cyclooxygenase 2 (COX2) Polymorphism at SNP RS20417 with Aspirin Resistance in Pakistani Patients with Ischemic Heart Disease - Mudassar Noor; Shah, Syed Zubair Hussain; Usman Nawaz; Qaiser Mansoor (Pakistan Armed Forces Medical Journal, 2024)
Objective: to find a link between a single nucleotide polymorphism (SNP) called rs20417 in the cyclooxygenase-2 gene and Aspirin resistance in Pakistani patients with heart disease. Study Design: Cross-sectional study. Place and Duration of Study: Pharmacology Department, National University of Medical Sciences, in collaboration with the National Institute of Heart Diseases and the Institute of Biomedical and Genetic Engineering in Islamabad Pakistan, from Oct 2018 to Dec 2021. Methodology: The study was carried out on 384 patients (272 males and 112 females) with ischemic heart disease. Patients who had been on Aspirin for at least seven days were selected using non-probability convenience sampling. Platelet aggregation was performed using a Transmission Aggregometer, with arachidonic acid as an agonist. DNA extraction was done using the kit method (Invitrogen, Thermofisher). Then, Polymerase chain Reaction, Restriction Fragment Length Polymorphism, and gel electrophoresis were used to identify SNP rs20417. Results: In this study, 14.0% (n=54) of ischemic heart disease patients were found to be Aspirin resistant, while 86.0% (n=330) were Aspirin responders. The genotyping of COX2 SNP rs20417 showed that 55.46% (n=213) of patients were homozygous with the GG genotype, 34.11%(n=131) had CG (heterozygous), and 10.41% (n=40) of patients were carriers of homogeneous (CC). Statistical analysis did not demonstrate a significant association of any of the alleles of the evaluated SNP with Aspirin resistance (p>0.05). Conclusion: In the Pakistani population, Aspirin resistance is not associated with any specific polymorphic form of Cyclooxygenase-2 at SNP rs20417.